Assessing the quality of airline websites and its impact on user satisfaction and continuance intention - Nazeer, Mohammad Nabeel (Department of Information Systems, 2024)
The growth of the Internet since the mid-1990s has created a variety of new business opportunities for many industries. The airline industry, one of the world's largest industries, responded to this growth by developing websites both to inform customers about their service offerings and to allow them to conduct e-commerce transactions. With the increasing number of airline companies using the Internet medium as a means of generating revenue, competition is always intense in the airline industry. In order to gain an advantage over their competitors, there is a need for airline companies to offer high quality websites that satisfy online users and entice them to continue using these websites in the future. Numerous studies have investigated the concept of website quality and used various research instruments to assess user-perceived website quality. However, very few of these studies have looked at the airline industry in particular. Furthermore, most of the research instruments used in these studies do not provide a comprehensive set of website quality attributes to assess an airline website. This research aims to investigate the quality of airline websites and its impact on user satisfaction and continuance intention. The literature surrounding these key concepts is reviewed and evaluated, and gaps therein are identified. A conceptual research model that incorporates a very comprehensive set of website quality attributes is then formulated. The model is based on an existing theoretical framework from literature, but is complemented with two additional variables, namely User Satisfaction and Continuance Intention. The study followed a quantitative research approach. A paper-based questionnaire, based on a strongly validated research instrument from literature, namely the WebQual, was administered to a large sample of students at a research university. Different statistical analyses were conducted on the data collected to empirically test the comprehensive conceptual model and validate it within the context of the airline industry. Results of the study indicated that the ease of use, usefulness, response time and entertainment components of an airline website have a significant direct influence on user satisfaction. It was further established that only the entertainment components of an airline website significantly influence an online user's intention to continue using the airline website. To gain a better understanding of trends that emerged within the data collected, a cross-region comparison of website quality was conducted. Results showed that there were significant differences between airline websites from four regions of the world in terms of trust. This is attributed to the ongoing concerns that online users have in terms of conducting monetary transactions on the Internet. A further comparison of website quality between the five most rated airline websites in the study revealed that there were significant differences between them in terms of their relative advantage, visual appeal, response time and intuitiveness. The significance of these results to both the academic arena and practitioners within the airline industry are discussed and avenues for further research suggested.